Digital Citizenship in Indonesia: Digital Literacy and Digital Politeness Using Social Media - Purwantiningsih, Ary; Riyanti, Dwi; Prasetyo, Danang (Universitas Negeri Malang, 2022)
This study aimed to describe the basis for strengthening global citizenship and increasing digital literacy in Indonesian society. This study used a qualitative approach with a descriptive type. The collection of primary data sources included books, scientific journals, manuscript publications, and internet news media using literature study techniques. The data obtained were analyzed using interactive techniques from Miles and Huberman. The results of the study showed that strengthening global citizenship was based on two aspects, namely digital literacy and digital ethics. Digital literacy was needed to improve people's ability to utilize technology supported by digital ethics. People's ability to understand information in the digital world was increasing with evidence of being able to distinguish between good material for consumption and information that must be avoided.